The impact of audit reports on auditor change: verification of the determining factors for auditor change in the portuguese context - Heliodoro, Paula (2020)
The issue of auditor change and its relation with the opinions issued in financial audit reports is a topic which has been gaining increasing importance in the accounting and auditing areas. The financial audit report represents the final materialization of an external and independent audit. As such, one expects that the opinion expressed by the auditor is not always that forecast by the shareholders or the management of the company being audited. This work attempts to ascertain whether or not a determining relation between a change in auditor and the issuance of qualified audit reports really exists in the Portuguese context, or, on the contrary, if other equally influential factors exist in relation to the said change. The conclusions drawn point to the existence of a significantly positive association between a qualified audit report and a change in auditor, although other relevant factors exist such as the company’s growth rate, governance model and the sector in which it operates